Growth, Thermal and Spectroscopic Studies of Bis-thiourea Nickel Barium Chloride Single Crystals - Hajiyani, Rakesh R.; Chauhan, Chetankumar K.; Joshi, Mihir J. (Asian Journal of Chemistry, 2017)
Bis-thiourea nickel barium chloride was synthesized and crystals were grown by slow aqueous solvent evaporation technique. The powder XRD analysis of grown crystal was suggested to have orthorhombic crystal structure. The unit cell parameters of grown crystal as: a = 9.70 Å, b = 10.68 Å and c = 17.95 Å. The contents of nickel and barium in the grown crystals was analyzed using EDAX. The presence of various functional groups was confirmed by FTIR spectroscopy studies. From the UV-visible spectrum, the material has about 90 % optical transparency in the entire visible region. From the thermogravimetric analysis, it was found that the crystals remained stable up to 170 ºC. The endothermic reactions were identified from the differential thermal analysis.